The Relationship of Family Readiness with the Quality of Life of Patients Suffering from Terminal Disease at Medan Murni Teguh Hospital - Seriga Banjarnahor (Institute of Computer Science (IOCS), 2019)
This study aims to identify the relationship between family readiness and the quality of life of patients suffering from terminal illness at the Murni Teguh Hospital in Medan. This study uses a descriptive correlational type of research using cross-sectional design. The population of this study were patients suffering from terminal illness who were hospitalized in the Murni Teguh General Hospital Medan using a sample of 30 people by means of purposive sampling. The results showed that 24 respondents (75%) were in the category of not ready to treat terminal illness patients and 8 people (25%) were in the prepared category and all terminal illness patients in the category of moderate quality of life were 32 people (100%). Statistical test results using the Spearman rank Correlation test obtained correlation value of 0.031 with a significance level of 5% (degree of confidence α = 95%). Value of 0.031 <0.05, then Ho is rejected or it can be concluded that there is a relationship between family readiness and quality of life for terminal illness patients with a correlation strength of 0.382. Suggestions for further research are expected to take a sample with a larger sample size so that research results are more representative.